(untitled) (World Economics and Finance Bulletin, 2023)
Success factors have become established as a significant paradigm within management and are part of the model by which the company’s activities are built. Today it is not only a unique approach to identifying the strengths and weaknesses of the company,1 but also a tool that allows you to improve the company’s performance and determine the contribution of each of its employees to the common cause. Success factors affect the activities of the organization’s employees, the divisions and elements of its structure, and the revenue from the sale of goods. The factors determining the success of the company reflect the most significant tasks of the enterprise and the benefits that the enterprise brings to the economy of the region and the country as a whole